Public enterprise in crisis : the future of the nationalised industries - Redwood, John. (Oxford : Blackwell, 1980)
This book deals with nationalization which is the process by which socialists hope to create greater equality amongst men
Includes index.
oo 24/01/2019
Loans
Keywords: Government ownership